Dampak Penggunaan Skincare terhadap Kejadian Akne Vulgaris Pada Mahasiswi Fakultas Kedokteran Universitas Sumatera Utara Angkatan 2022-2024 - Marshanda Febriana; Nova Zairina Lubis; Sufitni Sufitni; Tengku Helvi Mardiani (Lembaga Pengembangan Kinerja Dosen, 2026)
Acne vulgaris (AV) is a common dermatological condition affecting adolescents and young adults, with multifactorial causes including hormonal influences, increased follicular keratinization, excessive sebum production, and colonization by Cutibacterium acnes. External factors, particularly skincare behavior, are also considered to play an important role. The use of skincare products that are unsuitable for skin type or contain comedogenic ingredients such as mineral oil, lanolin, and certain silicones may clog pores and exacerbate acne. This study aimed to analyze the relationship between skincare product selection and usage behavior, types of skincare products used, and frequency of use with the occurrence of acne vulgaris among female medical students of the Faculty of Medicine, Universitas Sumatera Utara, cohorts 2022–2024. An analytical observational study with a cross-sectional design was conducted. Primary data were collected through an online questionnaire, while secondary data were obtained from the student directory. A total of 90 respondents were selected using stratified random sampling. Data analysis was performed using the Chi-square test. The results showed a significant association between skincare product selection and usage behavior and the occurrence of acne vulgaris (p = 0.043), as well as between the type of skincare products used and acne incidence (p < 0.001). However, no significant relationship was found between the frequency of skincare product use and acne vulgaris (p = 0.116). These findings indicate that appropriate product selection and type are more influential in acne development than usage frequency.